Counting gigs: How can we measure the scale of online platform work? - Agnieszka Piasna (European Trade Union Institute (ETUI), 2020)
The potential transformation of labour markets by the emergence of online labour platforms has triggered an intense academic, media and policy debate, but its true scale remains speculation. Nevertheless, adequate policy responses hinge on a good understanding of dynamics - something that will only grow in importance with the labour market crisis created by the COVID-19 pandemic. With technologically enabled remote work, growing demand for services such as food delivery or care, as well as rising unemployment and the financial strain on many workers, platform work may resume its rapid growth. Therefore, there is a need for good quality data on the prevalence of platform and other forms of precarious work in society. This working paper provides a critical assessment of different approaches to counting gigs; that is, estimating the scale of engagement in platform work in the general population. The aim is to examine the main obstacles encountered in previous studies, the reasons for surprising or contradictory results and possible sources of error, but also the lessons that can be learned for future research. This is illustrated with key research in this area, ranging from large projects conducted by national statistical offices to smaller scale independent research, from national to (nearly) global scale.
Keywords: 330; Labour market; structural change; telework; Coronavirus; Arbeitsmarkt; Strukturwandel; Telearbeit; Coronavirus